Implementasi Alat Pengering Sale Pisang Otomatis dan Sistem Penjualan Berbasis Digital Untuk Meningkatkan Kapasitas Produksi dan Omzet Penjualan di UMKM Rasa Alami, Kab. Subang - Susilawati Susilawati; Azhis Sholeh Buchori; Dwi Vernanda; Faadiyah Cheryl Rachelia (I-Com: Indonesian Community Journal, 2024)
UMKM Rasa Alami has succeeded in making a significant increase in the production and sale of bananas through the implementation of several innovations. These innovations include the use of a banana sale dryer which facilitates an increase in production volume, the adoption of an e-commerce based sales system which expands sales reach and simplifies the process, as well as the implementation of a financial system that can be accessed via smartphone which allows Rasa Alami MSME partners to control and record financial data every sales transactions. As a result of these innovations, there was an increase in sales banana production capacity from 1.2 tons in October to 1.8 tons in November, showing an increase of 55%. Meanwhile, sales turnover also increased by 50%, from Rp. 8,500,000 in October to Rp. 12,749,999 in November 2023.